Ovide, Flaubert, Proust : la remise du fuseau d'Arachné - Edi Zollinger (Flaubert: Revue Critique et Génétique)
Forty years ago, Margaret Lowe found in Madame Bovary a hidden “mise en scene” of the myth of Arachne as it is told in Ovid’s Metamorphosis. A long time before Lowe, already Marcel Proust had found the same silk of a spider and he used it in order to perform his own version of the myth. Continuing Flaubert’s weaving, Proust produces the voluptuous tissue, which he presents in a competition against Sainte-Beuve, the god of the nineteenth century’s literary critique, whom Proust wants to dethrone.